Development of Animated Video Learning Media Integrated with Quranic Verses on Molecular Shape Material for 11th Grade Student - Udzri, Muhammad Taufiq; Mawarnis, Elvy Rahmi; Sari, Dwivelia Aftika (Universitas Pendidikan Mandalika, 2024)
This research was motivated by the limited availability of learning media used as a source of student learning which has an impact on the quality and learning process. Learning media used by educators are still simple and non-technological. Therefore, it is necessary to develop a learning media to be used as an additional learning resource for students The learning media developed consists of animated videos integrated with verses from the Quran. The purpose of this research is to produce animated videos integrated with Quranic verses on molecular form material that are valid and practical. This research uses the Research and Development research method with the 4-D model (define, design, develop, and disseminate). Based on the results of the research conducted, it was found that 1) the animated video integrated with Quranic verses met the criteria of being very valid with a percentage of content feasibility on the material of 90.17%, content feasibility on the interpretation expert obtained a percentage of 95%, presentation feasibility obtained a percentage of 93.75%, presentation feasibility on the interpretation expert obtained a percentage of 100%, linguistic feasibility obtained a percentage of 92.41%, linguistic feasibility on the interpretation expert obtained a percentage of 96.87% and feasibility of grammatical obtained a percentage of 92.50%, 2) the animated video integrated with Quranic verses on molecular shape material has met the criteria of very practical with the results of student response questionnaires on the ease of use indicator obtained a percentage of 87.10%, the interest indicator obtained a percentage of 90.17%, the usefulness indicator obtained a percentage of 89.28 and time efficiency obtained a percentage of 90.62%. The results of this study indicate that the animated video developed can be used as a learning resource for students.